Conducting a physical postgraduate Orthopaedic exit examination during COVID-19 pandemic - Ismail, Imma Isniza; Mohd Saaid, Firdati; Liew, Siew Khei; Kamisan, Norazian; Harun, Mohd Hezery; Khirul Ashar, Nur Ayuni; Ab Halim, Ashraf Hakim (Universiti Putra Malaysia Press, 2024)
During the coronavirus disease 2019 (COVID-19) pandemic, the worldwide medical education system was affected tremendously due to the suspension of clinical activities and lockdown to prevent the spread of the disease. The delivery of clinical training was modified to alternative methods including online classrooms, recorded video, use of simulated patients and hybrid teaching. Several institutions worldwide chose to postpone their scheduled examination, which requires physical attendance or opted for virtual examination. Malaysian centralised postgraduate orthopaedic exit examination was postponed in 2020 and later recommenced in 2021 with three different centres across the country: north, east and central Malaysia. This article describes the preparation and challenges faced in conducting a face-to-face clinical exit examination for postgraduate orthopaedic candidates in Universiti Putra Malaysia in May 2021, during the Conditional Movement Control Order phase. The examination was a success, and no outbreak of COVID-19 was reported from the event.